Burden of the COVID-19 pandemic on adolescent mental health in the Lombardy Region, Italy: a retrospective database review - Antonio Clavenna; Massimo Cartabia; Ida Fortino; Maurizio Bonati (BMJ Publishing Group, 2024)
Background Previous research has assessed the impact of the COVID-19 pandemic on adolescent mental health (MH). How the pandemic changed healthcare resource utilisation for MH conditions was investigated less, however, in particular in Italy.Methods Data concerning outpatient visits in child and adolescent mental health services (CAMHSs), access to emergency departments (EDs), hospital admissions and drug prescriptions collected in administrative databases of the Lombardy Region, Italy, concerning adolescents 12-17 years old and occurring in the 2016-2021 period were analysed.Annual and monthly prevalence of healthcare (CAHMS/ED visits/hospital admissions) use for MH conditions and of psychotropic drug prescriptions were estimated. A negative binomial regression model was used to model the pre-pandemic monthly number of prevalent cases by gender. The total number of pandemic (1 March 2020 to 31 December 2021) cases predicted from the model was compared with the number of observed cases.Results The overall annual rate of healthcare service utilisation slightly increased in the 2016-2019 period (from 63.8‰ to 67.8‰), decreased in 2020 (57.1‰) and returned to values similar to 2016 (64.9‰) the following year. A 2% relative increase was observed in girls, and a 10% decrease in boys, when comparing the prevalence in 2021 with that in 2019. Differences between genders were particularly evident for ED attendance, with an observed/predicted cases ratio in 2021 of 0.81 (95% CI 0.79 to 0.83) in boys, and 1.18 (95% CI 1.16 to 1.20) in girls, and for psychotropic drug prescriptions (0.83 (95% CI 0.82 to 0.84) and 1.24 (95% CI 1.23 to 1.25), respectively).Conclusions The current study confirms that the use of health services for MH conditions during the COVID-19 pandemic increased among adolescent girls but decreased among boys, and that gender differences emerged in the MH impact of the pandemic.